MATHEMATICAL MODELING OF SYNTHETIC UNIT HYDROGRAPH CASE STUDY: CITARUM WATERSHED - LAMBOK ANGELA SUKRAININGTYAS (NIM :10108023); Pembimbing I : Prof. Dr. Edy Soewono; Pembimbi, ADISKA
Deriving unit hydrograph is an important thing to do in analyzing watershed hydrologic response of a rainfall event. In most cases hourly measures of stream flow data needed in deriving unit hydrograph are not always available. Hence,it is needed to develop methods for deriving unit hydrograph for ungaged watershed. Methods that have evolved are based on theoritical or empirical formulas relating hydrograph peak flow and timing to watershed characteristics. These are usually referred to Synthetic Unit Hydrograph. The two gamma probability density function is used as the mathematical representation of unit hydrographs in Citarum Watershed. The resulting model is adjusted with real field condition by translation and scaling. The two parameters are determined using Particle Swarm Optimization Method. The resulting two parameter gamma probability density function of can be used as a good synthetic unit hydrograph to predict unit hydrograph of Citarum Watershed.